Islamic ethics of manufacturing - Amanullah, Muhammad (2012)
The business of making goods in large quantities in factories, by and large, is considered to be a modern phenomenon. With the development of different types of advanced technology and machinery this phenomenon has been tremendously increased during last few decades all over the world. All these developments have led to decrease of the involvement of human labor in every type of factories. But because of diversity and vastness of these industries they still require many skilled and non-skilled workers to run them. In the past complaints have been filed against many factory owners by their workers and employees. Some of these complaints were related to ethical treatment of the owners of these factories. Responding to these complaints, many well-known companies and organizations have developed their codes of ethics to deal with their workers, employees and customers. Islam also has a set of ethics that should be followed by the manufacturers or owners of these factories. Discussing relevant Qur’anic verses, ahadith of the Prophet (p. b. u. h.), and Islamic principles this paper highlights these manufacturing ethics aiming to produce a comprehensive Islamic code of ethics for manufacturing; which could be used by Muslim manufacturers all over the world, and which also could be a good reference for non-Muslim manufacturers to improve their codes of ethics for manufacturing.